Degradation of notarial deeds in criminal cases (analysis of Sidoarjo district court decision number: 862/Pid.B/2019/PN Sda) - Ivanda Aprilia; Miftakhul Huda (INFOKUM, 2024)
This study aims to determine the legal consequences of misuse of notary authority to make deeds. Notaries in carrying out the duties of their office must be careful and careful in making deeds, so that the deeds they make are not legally defective because they must be accountable to the general public and so as not to harm others. This research uses a conceptual approach and a legal approach. Using a conceptual approach, researchers refer to legal principles related to the concept of the state of letters in the case of forgery of letters. The legal approach is carried out by reviewing related laws and regulations. This research is analytical in nature that studies the purpose of law, the values of justice, the truth of the rule of law, legal concepts and legal norms according to the position of deeds in relation to the implementation of the duties of unscrupulous authentic deed makers . The results of this study conclude that the criteria for a notary deed to become an authentic deed have been regulated in the law, so that Notaries who are officials who are authorized to make authentic deeds must always pay attention to the procedures for making deeds in accordance with applicable laws. When the deed loses its evidentiary power, it can be relegated to a deed under hand, or become invalid or become null and void. So the Notary Public must be responsible for his negligence in exercising his authority. If the authentic deed in its making is a legal defect caused solely by the fault of the Notary and then the deed in Court is declared inauthentic, or invalid, or becomes null and void or relegated to a deed under hand, then the Notary must be concerned be liable for the error caused by the forgery of the deed.